(untitled) (Research, Society and Development, 2022)
Iron is an essential mineral for the human being and its functionality in the human body is related to oxygen transport, Deoxyribonucleic Acid (DNA) synthesis, and energy metabolism, it also helps people to have a better athletic performance, contributes to the increase of functions related to the reasoning capacity, memory, and learning, among others. The iron used by the body is obtained in two ways: from the diet and from the recycling of senescent red blood cells. Deficiency of this mineral has consequences for the entire body, the most significant manifestation being anemia. However, the excess of iron in the body is very harmful to tissues and cells, since it reacts with oxygen, promoting the formation of hydroxyl radicals and superoxide anions. In this view, the objective of this paper is to present the importance of iron in the human organism, approaching the damage caused by the lack or excess of iron and possible solutions. Thirty-three articles were used, which met the inclusion criteria, which required academic articles in English, Spanish, and Portuguese, published in the last five years retrospectively. It was concluded that iron is fundamental for cell function and energy metabolism, and its regulation is necessary. It has been shown that lack of iron is associated with deficiency anemia, fatigue and dyspnea, and metabolic complications, while its excess may be widely associated with cellular toxicity and tissue damage. The importance of clinical assessment of iron levels and professional monitoring to ensure a good quality of life is then emphasized.